New Beauveria bassiana aerial conidia-based bioinsecticide obtained by spray-dried microencapsulation of the entomopathogenic fungi in biopolymers for crop protection - Matheus G. de Jesus Seabra; Tárcio S. Santos; Camila de Souza Varize; Eliana B. Souto; Patrícia Severino; Marcelo da Costa Mendonça (Egyptian Journal of Biological Pest Control)
Abstract Background Due to their environmentally friendly character, entomopathogenic fungi (EPF) are becoming increasingly used as microbial agents in biological pest control over chemical pesticides. However, EPF are sensitive to the influence of abiotic factors, such as temperature, radiation, and humidity. To improve their efficiency as bioinsecticides, in this work, the development of a new microparticles-based formulation loading EPF conidia (B. bassiana aerial conidia) into sodium alginate/maltodextrin microparticles obtained by spray-drying was proposed. Different concentrations of both polysaccharides were tested to reach the optimal ratio and ensure a high viability of encapsulated conidia. Results All the produced formulations showed a moisture content < 10% and water activity (aw) < 0.4. Microparticles obtained with 2% sodium alginate and 8% maltodextrin were able to retain 89.5% of the viability of encapsulated conidia, thus being selected for further characterization. Scanning electron microscopy showed microparticles with a smooth surface, varied sizes, and irregular morphology. Microparticles retained 5.44 × 108 conidia/g, presented high hygroscopicity and high suspensibility rate, yet low wettability and water activity (aw) of 0.33. The pH value ranged from 6.46 to 6.62. Microparticles were able to complete release the loaded conidia after 30 min, under constant stirring. When exposed to thermal stress (45 °C), microparticles promoted thermal protection to conidia. Enhanced pathogenicity of B. bassiana conidia against P. xylostella was also confirmed achieving 83.1 ± 5.5%, whereas non-encapsulated conidia reached only 64.8 ± 9.9%. Conclusions This study confirms that the encapsulation of B. bassiana fungus conidia in sodium alginate/maltodextrin microparticles by spray-drying is a promising technological approach for the biological control of agricultural pests.